2014
DOI: 10.1017/jwe.2013.34
|View full text |Cite
|
Sign up to set email alerts
|

The Determinants of Chemical Input Use in Agriculture: A Dynamic Analysis of the Wine Grape–Growing Sector in France

Abstract: This article examines the determinants of chemical consumption by French winegrowers on an individual basis. We introduce criteria relating to the structure of vineyards and the financial situation of the winegrowers. Using data from the Farm Accountancy Data Network (FADN-RICA) for the period 2002-2007 from an annual sample of 607 winegrowers, we study the different factors that encourage winegrowers to use chemical inputs to protect or increase the yield of their vines. Drawing on transversal and longitudina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 33 publications
0
11
0
1
Order By: Relevance
“…Fernandez-Cornejo and Ferraioli (1999) and Wu (1999) showed that educated and younger farmers apply fewer pesticides because they are more aware of their drawbacks. Aubert and Enjolras (2014a) and Mishra et al (2005) also proved that productive farms and farms located in less-favored areas are more prone to pesticide use. Indeed, such areas face natural handicaps (e.g., lack of water and unfavorable climate) or are mountainous or hilly, which increases production risk.…”
Section: Two Widely Used Risk Management Instruments: Crop Insurance and Pesticidesmentioning
confidence: 92%
See 3 more Smart Citations
“…Fernandez-Cornejo and Ferraioli (1999) and Wu (1999) showed that educated and younger farmers apply fewer pesticides because they are more aware of their drawbacks. Aubert and Enjolras (2014a) and Mishra et al (2005) also proved that productive farms and farms located in less-favored areas are more prone to pesticide use. Indeed, such areas face natural handicaps (e.g., lack of water and unfavorable climate) or are mountainous or hilly, which increases production risk.…”
Section: Two Widely Used Risk Management Instruments: Crop Insurance and Pesticidesmentioning
confidence: 92%
“…For instance, risk averse farmers are more willing to apply pesticides (Pannell 1991). Pesticide applications can also be tactical after unfavorable weather conditions prone to crop diseases (Aubert and Enjolras 2014a;Horowitz and Lichtenberg 1993;Mishra et al 2005).…”
Section: Two Widely Used Risk Management Instruments: Crop Insurance and Pesticidesmentioning
confidence: 99%
See 2 more Smart Citations
“…Second, improved equipment and spraying technology can reduce emissions from pesticide use. For example, Aubert and Enjolras (2014) show in an analysis for French wine producer that the age of the equipment is significantly increasing the likelihood of overapplication of pesticides. Investment in better technologies remains an important policy measure even in developed countries.…”
Section: Pesticide Taxes As Part Of a Coherent Set Of Policiesmentioning
confidence: 99%